Tectonic timing of emplacement of the South Mountain Batholith, southwestern Nova Scotia, Canada - Clarke, D. Barrie; MacDonald, Michael A.; McKenzie, Colin B. (Atlantic Geoscience)

(untitled) (Atlantic Geoscience Society, 2025)
The South Mountain Batholith (SMB) of southwestern Nova Scotia is the largest intrusion in the Appalachian orogen. Some structures in its Meguma Supergroup country rocks pre-date emplacement of the SMB, some structures in the country rocks and batholith are synchronous with emplacement and cooling of the granite magma, and other structures in the country rocks and intrusion post-date emplacement. In this paper, we compile an inventory of all such structures, over a wide range of length scales, and evaluate each one in terms of its bearing on the tectonic conditions of emplacement of the SMB. Early structures in the country rocks may include faults that controlled the emplacement of the SMB and include folding (F1) and axial planar cleavage (S1) belonging to the Neo-Acadian orogeny. Structures in the country rocks temporally related to granite emplacement include cross-cutting relationships, annealing of cleavage, growth of porphyroblasts in the contact aureole, fabrics in contact migmatites, granite dykes cutting the country rocks, deformation aureole fabrics, late flexural slip, a putative oroclinal bend, and possibly the structures hosting the Meguma terrane gold deposits. Structures in the granites themselves include shapes of Stage I plutons, foliations in Stage I plutons, development of augen textures, shapes of Stage II plutons, foliations in Stage II plutons, “folding” in the Halifax Pluton, internal granite-granite contacts, ring schlieren, textures of immiscible sulphides in the granites, 2-D and 3-D shapes of gravity anomalies, paucity of high-T deformation microstructures, and undulose extinction in quartz. Late structures, affecting the country rocks and the granites, include joints, and barren or mineralized faults and shear zones. Not all structures have a bearing on the tectonic timing of emplacement of the SMB, but the SMB indisputably post-dates the main Neo-Acadian F1–S1 deformation. The most problematic issues concern the origin of late brittle and ductile deformation features in the SMB (augen granites, deformation aureoles, joints, faults, shear zones, and related mineral deposits) and whether they are the result of waning Neo-Acadian deformation, internal adjustments, uplift, gravitational collapse, or other regional-scale tectonics.